2021
DOI: 10.3233/shti210031
|View full text |Cite
|
Sign up to set email alerts
|

Is Consent Not a Consideration for Instant Messaging?

Abstract: Background: Recently there has been a steady increase in the use of Instant Messaging (IM) as a means of providing health and healthcare services. This growth has been particularly rapid during the ongoing COVID-19 pandemic. Many reports indicate informal services using IM, in particular WhatsApp, have arisen spontaneously, in the absence of any formal guidelines and little consideration of consent. This study documents the consent practices of healthcare professionals using IM for clinical activities in Distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…A recent review of consent practices when using WhatsApp found only 18 papers that reported obtaining either written or verbal consent for sharing information and/or images [48]. At one academic hospital, 97% of doctors surveyed did not obtain consent for sharing patient information by instant messaging [49].…”
Section: Consentmentioning
confidence: 99%
“…A recent review of consent practices when using WhatsApp found only 18 papers that reported obtaining either written or verbal consent for sharing information and/or images [48]. At one academic hospital, 97% of doctors surveyed did not obtain consent for sharing patient information by instant messaging [49].…”
Section: Consentmentioning
confidence: 99%
“…One plausible intervention is to use telemedicine to support home‐based follow‐up for women after c‐section delivery. All of the strategies identified in global reviews of teledermatology which included postoperative monitoring [21, 22] or of telemedicine for SSI detection specifically [23] required patients owning phones to engage in the intervention. This may not be feasible in rural SSA, given that mobile phone ownership is associated with wealth [24] and incomplete cell network coverage [25].…”
Section: Introductionmentioning
confidence: 99%
“…While a variety of mHealth applications (mobile health products and technology solutions that aim to improve patient care and healthcare delivery) are built to meet certain ethical and regulatory standards, the use of WhatsApp for the coordination of medical care does pose ethical and regulatory concerns including patient confidentiality as well as worries around data “security, record keeping, and storage” [ 32 , 34 ]. Patient's personal information and healthcare data are potentially at risk at several levels, including during “storage on servers, and on the sender's and receiver's phones” [38] . That said, any digital platform is potentially at risk of third parties accessing patient's data.…”
Section: Discussionmentioning
confidence: 99%